2021
DOI: 10.1007/s12070-020-02295-w
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and Gustatory Dysfunction in COVID-19 Patients: A Tertiary Care Institute Experience in India

Abstract: COVID-19 epidemic has varied spectrum of symptoms. With this study we aim to evaluate prevalence of Olfactory and Gustatory dysfunction in COVID-19 patients. To assess Olfactory and Gustatory dysfunction in COVID-19 Patients in Indian Population. Settings and Design: Prospective observational study. RT-PCR proven COVID-19 patients were enrolled in the study. Detailed history and olfactory function and Taste function were evaluated. Patient with symptoms of olfactory dysfunction were subjected to fill (sQOD-NS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…The remaining 18 studies were conducted in other regions (a pie chart showing distribution is included in the supplementary data provided— S1 Fig ). 10 studies were conducted in Asia: Turkey (n = 5) [ 18 , 27 , 38 , 41 , 50 ], Iran (n = 2) [ 22 , 55 ], India (n = 2) [ 33 , 52 ], Israel (n = 1) [ 32 ]. Four studies were conducted in North America: United States (n = 4), [ 21 , 42 , 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 18 studies were conducted in other regions (a pie chart showing distribution is included in the supplementary data provided— S1 Fig ). 10 studies were conducted in Asia: Turkey (n = 5) [ 18 , 27 , 38 , 41 , 50 ], Iran (n = 2) [ 22 , 55 ], India (n = 2) [ 33 , 52 ], Israel (n = 1) [ 32 ]. Four studies were conducted in North America: United States (n = 4), [ 21 , 42 , 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in Africa: Egypt (n = 2) [ 34 , 49 ], and two in South America: Brazil (n = 1) [ 53 ], Chile (n = 1) [ 15 , 53 ]. Of the 44 studies, twenty-five (56.8%) reported no funding requirements for the project [ 16 , 18 , 19 , 22 , 27 30 , 32 , 33 , 39 , 40 , 42 47 , 49 51 , 53 , 58 ]; six (13.6%) studies reported funding for the project (sources included academic institutions, government and not-for-profit organizations) [ 15 , 24 , 25 , 31 , 48 , 57 ], and thirteen (29.5%) did not report whether funding was provided [ 17 , 21 , 23 , 26 , 37 , 38 , 52 , 54 56 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies reported anosmia prevalence in eighteen cohorts with a total of 7,247 COVID-19 patients from regions where the D614 virus was dominant: three studies from Kuwait and Singapore [42][43][44] and twelve from India or Pakistan. [45][46][47][48][49][50][51][52][53][54][55][56] We compared such data with the results obtained in 25 studies reporting on 25 cohorts with a total of 9,626 South Asian patients from the Indian subcontinent (India and Bangladesh) and Oman, when the G614 virus had become dominant (Table 1, illustrated in Fig. 3A, B).…”
Section: Systematic Review and Meta-analysis Of South Asian Studiesmentioning
confidence: 99%